O capital monopolista-financeiro e a grande recessão - Palludeto, Alex Wilhans Antonio; Andrade, Rogério Pereira de (Estudos Econômicos (São Paulo), 2014)
Resenha do livro: FOSTER J. B.; MAGDOFF, F. The Great Financial Crisis: Causes and Consequences.New York: Monthly Review Press, 2009.